Open science practice support: lessons from the UPM library - Iberahim, Zubaidah; MD Ishak, Mohamad Syahrul Nizam; Abdul Latif, Norhafizah (Perpustakaan Universiti Sains Malaysia, 2025)
Open Science is a global movement that promotes transparent and accessible research, open to all. This study examines how the University Putra Malaysia (UPM) Library facilitates open science through collaborative efforts at the university level, with a focus on open data and open access. A qualitative approach was adopted, involving an analysis of official documents, internal reports, and interviews with librarians and researchers who participated in the Open Science Road Tour. The results show that the UPM Library has taken several important steps to support open science. These steps include creating two institutional repositories (UPMIR and PutraRDRepo), building the PSAS Information Hub, running Open Science Month, conducting faculty road tours, and conducting training sessions with national and international partners. These efforts have led to the increased use of open platforms, improved data management, and greater awareness of open science among researchers. Data from PutraRDRepo indicates strong growth in usage and international access, whereas feedback from researchers shows that they value the library's support. This study demonstrates that libraries play a crucial role in building open science infrastructure, raising awareness, and supporting researchers. It recommends expanding training to include students, especially postgraduate students, enhancing advisory services, and establishing a university-level open science committee. These suggestions could greatly benefit other libraries aspiring to support open science in their institutions.